Moisture insulation with clay of underground buildings on the example of modern era fortifications and Warsaw Elizeum - Narębski, Lech (Protection of Cultural Heritage, 2020)
Based on the analogy of the structures of underground buildings – the Warsaw Elizeum and many fortress buildings from the eighteenth to the nineteenth century, the article is an attempt to present an overview of historical methods of protecting their interiors against moisture penetrating from embankments, condensation, pulled up by capillaries or diffusing from the ground. The methods of moisture protection in the modern fortifications were developed over 4 centuries of its development (16th – 19th c.), as a result of gradual accumulation of experience and engineering knowledge. Important elements of these protections were clay/loam cladding and corridors running around underground spaces, which had not only transport function, but also served as an insulation and ventilation buffer. Underground buildings, properly designed for extremely unfavorable conditions of use, can last thanks to the delicate balance, which is very easy to disturb. The first condition of this balance is to maintain a proper ventilation and heating regime for condensation-prone interiors. At the end, care and maintenance activities aimed at stopping the progressing degradation of the building are proposed, and indications for the research program and pre-design assumptions for future necessary renovation and conservation works are outlined.